PENGARUH MANAJEMEN KESISWAAN TERHADAP KEAKTIFAN PESERTA DIDIK DALAM KEGIATAN SEKOLAH - Putri, Elsya Amelia; Umma, Sara Zakiyyatul; Aprilian, Wahyu Rizky; Syifa', Azizah Lailatus; Minan, Rifi Rohmatul; Wulandari, Ayu (LPPM UM Metro, 2025)
This research aims to analyze the influence of student management on student engagement at Sunan Giri Menganti High School. A quantitative approach was used through the distribution of questionnaires aimed at educators. Data were obtained from 36 respondents including teachers and vice principals. The research instrument was a Likert scale questionnaire that had been tested for validity and reliability. Data analysis was conducted using the Spearman's Rho test, linearity test, and simple linear regression. The results showed a strong and significant relationship between student management and student engagement, with a correlation of 0.713. The regression equation Y = 13.414 + 0.815X indicates that every increase in the quality of student management is followed by an increase in student engagement. The R Square value of 0.626 indicates that 62.6% of student engagement is influenced by student management, while the rest is influenced by other factors. These findings confirm that structured student management, from planning to evaluation, plays an important role in encouraging active student participation in both learning and school activities.